PENGARUH SPESIES BAKTERI DAN RATIO SPERMATOZOA/BAKTERI TERHADAP VITALITAS SPERMATOZOA MANUSIA SECARA IN VITRO - Sukarjati Sukarjati; Hamdani Lunardhi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2001)
The effect of some pecies of bacteria and sperm/bacteria ratio on sperm vitality has been studied. Four species of bacteria were used in this study: Stapylococcus epidermidis, Streptococcus faecalis, Enterobacter aerogenes were obtained from semen culture of infertile men and E. coli was obtained from prostaltic fluid culture from men with prostat and urinary system disturbances. Five semen samples fulfilling the WHO criteri (1992) were used in this study. After preparation by Percoll gradient-column method, sperm were inoculated in a microplate with Stapylococcus epidermidis, Streptococcus faecalis, Enterobacter aerogenes and E. coli under the sperm/bacteria ratio 1:10 and 1:1000. Sperm vitality was observed immediately, 3 and 6 hours after inoculation. At the second experiment, the detrimental influence of bacteria on sperm was prevented by adding penicillin. Result of this study indicated that Stapylococcus epidermidis, Streptococcus faecalis, and Enterobacter aerogenes were not affected on the sperm vitality. The effect of E. coli on sperm vitality occurred at the ratio of sperm/bacteria 1:10 after 3 and 6 hours incubation and at the ratio of sperm/bacteria 1:1000 occurred after 6 hours incubation. It might be concluded that the negative influence of bacteria on sperm vitality in vitro, is dependent in species of bacteria, bacteria concentration, and time of incubation. The most detrimental effect on sperm vitality was shown by E. coli at the ratio of sperm/bacteria 1:10 after 6 hours incubation. The detrimental effecr was not prevented bt the addition of penicillin.